Clinical electrophysiology and visual outcome in optic nerve hypoplasia. Issue 8 (2nd December 2009) - McCulloch, D L; Garcia-Filion, P; Fink, C; Chaplin, C A; Borchert, M S
Abstract : Aims: In optic nerve hypoplasia (ONH), the extent of functional loss of retinal ganglion cells cannot be determined by ophthalmoscopic examination. The prognostic value of visual electrodiagnostic tests in infants and toddlers with ONH was assessed by comparison with visual outcome. Methods: 85 participants with ONH had electroretinogram (ERG) and visual-evoked potential (VEP) testing to flash and to pattern-reversal checks and ocular fundus photography prior to 36 months of age. These initial measures were compared with visual acuity outcomes at 5 years of age in the better-seeing eye. Results: Visual outcomes ranged from normal to no light perception. Electrodiagnostic tests with prognostic value were: the amplitude of the flash VEP (Spearman's rank correlations, p<0.001), the threshold category of stimulus (flash or check size) that elicited a VEP (p<0.001) and the amplitude of the N95 component of the pattern ERG (PERG) to 4-degree checks (p<0.02). Optic nerve size and co-existing pallor were also significant correlates. Stepwise regression analysis composed a best prediction model from VEP threshold category, optic nerve size and optic disc pallor (R 2 =58%; p<0.001). Conclusions: Optic disc diameter, observation of disc pallor, VEP and PERG testing in infancy are useful for establishing the visual prognosis at 5 years of age in children with ONH. This is consistent with the notion that these parameters are related to the anatomic and functional preservation of retinal ganglion cells.